PERKEMBANGAN EKONOMI KABUPATEN/KOTA DAN KINERJA KEUANGAN DAERAH DI JAWA TENGAH PADA ERA OTONOMI - Firmansyah . (Jurnal Bisnis dan Ekonomi, 2014)
The broad distribution of authority from central to local local government, which is known as autonomy, in impelentation of the development and budget management, is aim to accelerate the achievement of public welfare through serviceimprovement, empower and enhance the participation of community, and in addition to increase regional competitiveness. Overall, the performance of Central Java economy is good, which can be seen in the development of some indicators suchas economic growth, the increase of per capita income, a decrease in the number of the poor as well as an increase in the Human Development Index. However, the indicators of regions is exist and and the income inequality of household arewidened in autonomy era. As the district/city level in Indonesia in general, the financial independence of the districts/cities in Central Java province are below 30 per cent with the capital expenditure below 25 per cent. Although most of thedistricts/cities have the ability to cover the expenditure with revenue, but the budget surplus policy is not necessarily appropriate by the reason of excessive austerity, lead to lack of attention of the government especially in infrastructureinvestment spending.Keywords: Economic growth, inequality, local budget performance